2019
DOI: 10.1111/jgs.15785
|View full text |Cite
|
Sign up to set email alerts
|

The 5Ts: Preliminary Development of a Framework to Support Inclusion of Older Adults in Research

Abstract: Background/Objectives To address the underrepresentation of older adults in clinical research, the National Institutes of Health will require investigators to include individuals across the lifespan. As investigators from other fields endeavor to recruit participants who are more representative of the patient population, geriatricians may have the opportunity to influence a broad range of research studies in older adults. Our aims were to elicit challenges to inclusion of older adults in clinical research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 18 publications
(25 reference statements)
2
47
0
Order By: Relevance
“…A single site study from 2007 to 2014 observed a 222% increase in acute dysphagia referrals for hospitalised patients 90 years and older [24]. Participant recruitment requires careful planning to ensure the oldest old are represented in countries with ageing populations, such as applying the 5Ts framework [19]. A recent systematic review on the effects of age on swallowing identified only one third of published studies (38/107) recruited adults over 85 years old [8].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…A single site study from 2007 to 2014 observed a 222% increase in acute dysphagia referrals for hospitalised patients 90 years and older [24]. Participant recruitment requires careful planning to ensure the oldest old are represented in countries with ageing populations, such as applying the 5Ts framework [19]. A recent systematic review on the effects of age on swallowing identified only one third of published studies (38/107) recruited adults over 85 years old [8].…”
Section: Agementioning
confidence: 99%
“…Underrepresentation of very old adults can also limit the clinical application of research findings. The 5Ts framework (target population, team, tools, time, and tips) was recently developed to address barriers to recruitment of older adults in clinical research and provide a strategy for inclusion [19]. This framework complements the 5Ms (mind, mobility, medications, multicomplexity, and matters most to me) which promotes the key competencies of geriatrics in clinical practice [20].…”
Section: Introductionmentioning
confidence: 99%
“…All of these issues, together with best practice strategies to overcome obstacles to the recruitment and retention of older adults in aging research, were discussed in the December 2008 issue of this journal . A decade later, it is gratifying to see three articles address the inclusion of older adults in research . Timing is perfect given major progress at the national level in the form of a new NIH (National Institutes of Health) policy effective as of January 25 2019 mandating the inclusion of older adults into all NIH‐supported research involving human subjects when scientifically appropriate.…”
Section: Major Progress Toward Inclusion Of Older Adults In Researchmentioning
confidence: 99%
“…The posting by NIA of a funding opportunity announcement for applications related to the science of examining diversity, recruitment, and retention in aging research should greatly accelerate progress . Also, the 5Ts Framework described by Bowling et al in this issue provides practical insights into addressing some of the barriers to participation by non‐geriatrician investigators and research staff without experience in aging research and may also help frame future research on this topic.…”
Section: Ensuring Recruitment Feasibility and Promoting The Science Omentioning
confidence: 99%
See 1 more Smart Citation